2023
DOI: 10.1002/jsfa.13092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a mixture of glycerol monolaurate and cinnamaldehyde supplementation on laying performance, egg quality, and antioxidant status in laying hens

Lanlan Li,
Yue Zhu,
Shuangshuang Zhang
et al.

Abstract: BACKGROUNDThis study aimed to determine the effects of a mixture of glycerol monolaurate and cinnamaldehyde (GCM) supplementation on the laying performance, egg quality, antioxidant capacity, and serum parameters of laying hens. A total of 1120 14‐week‐old Jingfen‐1 strain laying hens with similar performance were randomly allocated to four dietary treatments: control, and GCM groups supplemented with 250, 500, or 1000 mg kg−1 for 12 weeks.RESULTSCompared with the control group, GCM‐supplemented groups signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Colonized Bacillus, Clostridium , and Lactobacillus are often used as probiotics in the poultry industry ( Liu et al, 2023 ). A study has shown that lactic acid bacteria, as a beneficial bacterium, can improve the feed efficiency of chickens ( Yan et al, 2017 ), which is consistent with the results of our previous study that 1,000 mg/kg GCM supplementation can significantly improve the laying performance, egg quality and serum antioxidant status of laying hens ( Li et al, 2024 ). It was found in this experiment that Clostridia was significantly enriched in 1,000 mg/kg GCM group using LEfSe.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Colonized Bacillus, Clostridium , and Lactobacillus are often used as probiotics in the poultry industry ( Liu et al, 2023 ). A study has shown that lactic acid bacteria, as a beneficial bacterium, can improve the feed efficiency of chickens ( Yan et al, 2017 ), which is consistent with the results of our previous study that 1,000 mg/kg GCM supplementation can significantly improve the laying performance, egg quality and serum antioxidant status of laying hens ( Li et al, 2024 ). It was found in this experiment that Clostridia was significantly enriched in 1,000 mg/kg GCM group using LEfSe.…”
Section: Discussionsupporting
confidence: 89%
“…It was found in our previous study that glycerol monolaurate and cinnamaldehyde mixture ( GCM ) addition can significantly improve egg quality and serum antioxidant status in laying hens ( Li et al, 2024 ). Therefore, the purpose of this research was to evaluate the responses of intestinal morphology, immunity, antioxidant status and cecal microbiota to the GCM addition in laying hens, and to provide a new way to further explore the mechanism of GCM improving intestinal health.…”
Section: Introductionmentioning
confidence: 99%